Study of general health of traumatic nursing team members of Bam one year after earthquake - F Sistanehei; Z Goudarzi; R Rezapour; A Mehran; A Mahmoodi; M gheri Tafreshi; H Ahmadvand; Y Shimodaira; M Ohara; K Emora (Tehran University of Medical Sciences, 2005)
Introduction: It is necessary to understand that psychological reactions after a natural disaster are as complex as disaster itself. Following a catastrophic earthquake like Bam's, such reactions can be seen in nursing team members as well. Materials and Methods: This study is a descriptive cross sectional analytic research, conducted with cooperation of Japanese Nursing Association to identify somatic and psychological problems of nursing team members of Bam. A total of 92 members of nursing team affiliated to healthcare centers of Bam were studied. Data collection tools were 2 questionnaires first for evaluating demographic characteristics and general health and second- questionnaire of Goldberg and Williams- for evaluation of four domains of psychosomatic problems, anxiety and insomnia, psychosocial functioning and severe depression. Each domain contained seven questions, each scored from 0 to 3 based on Likert score. Complete score of general health was 0-84. Scores were classified in four groups: 0-20 as optimal, 21-4 as approximately optimal, 41-6 as approximately suboptimal and 61 and higher as suboptimal. Results: One year after the earthquake, evaluation of general health of nursing team members showed 30.3% of subjects had optimal psychosomatic status, 34.8% had moderate problems of anxiety and insomnia, 40.2% had approximately optimal psychosocial functioning and 44.2% of subjects were not severely depressed. Overall, 38.4% of nursing team members had approximately optimal general health. Conclusion: This study showed that following a catastrophic earthquake, most of the victims suffer from several psychological and somatic reactions. In addition to on time rescue procedures, other important allaying factors are cultural and religious values and believing in God.